Facilitating heart transplantability in an end-stage heart failure patient with brain abscess and infected left ventricle assist device—A unique case report. (2020) - Ibrahim, Mohamad; Arafat, Shawqi; Rojas, Sebastian V.; Schramm, René; Gummert, Jan F.; Morshuis, Michiel; Fox, Henrik
Highlights: Therapeutic scope in a patient designated with no therapeutic option left. Strategy ineligible for heart transplantation for uncontrolled infection. Extraordinary case elucidating our unestablished treatment strategy. Finally after treatment patient was listed for heart transplantation. Abstract: Introduction: Heart transplantation is the desired therapy in end-stage heart failure (HF) and in patients with left-ventricular assist devices (LVAD) suffering from life-threatening complications on device. Comorbidities are frequent in end-stage HF and may refrain the patient from being listed for heart transplantation such as infections making surgery impossible. Presentation of case: We report the first case of a patient with proven LVAD system infection who additionally suffers from a brain abscess that made listing for heart transplantation impossible, leaving this patient no apparent treatment option. Conclusion: Our extraordinary treatment strategy finally resolved both the brain abscess and LVAD system infection through extensive conservative long-term treatment facilitating this patient to be finally listed for regular heart transplantation and sustained relieve of systemic infection.